Postoperative CEA is a better prognostic marker than CA19-9, hCGβ or TATI after resection of colorectal liver metastases - Reetta Peltonen; Pia Österlund; Marko Lempinen; Arno Nordin; Ulf-Håkan Stenman; Helena Isoniemi (Tumor Biology)
Liver metastases of colorectal cancer can be operated with a curative intent in selected cases. However, more than half of the patients have a recurrence. The aim of this study was to evaluate the prognostic and predictive value of carcinoembryonic antigen (CEA), carbohydrate antigen 19-9 (CA19-9), human chorionic gonadotropin β (hCGβ) and tumour-associated trypsin-inhibitor (TATI) in colorectal cancer patients before and 3 months after resection of liver metastases. Marker concentrations were determined in blood samples from 168 colorectal cancer patients, who underwent liver resection between the years 1998 and 2007 at Helsinki University Hospital, Finland. The samples were taken before and 3 months after curative resection. Increased concentrations of CEA (>5 µg/L) and hCGβ (>1 pmol/L) 3 months after liver resection correlated with recurrence and impaired overall survival and increased CA19-9 (>26 kU/L) with impaired overall survival, but postoperative TATI was not prognostic. Preoperatively elevated CEA and CA19-9 correlated with impaired overall survival, but not with recurrence. Neither preoperative hCGβ nor TATI was prognostic. In conclusion, CEA is a useful prognostic marker, when measured 3 months after resection of colorectal liver metastases. CA19-9 also has prognostic significance and may have additional value.